Resource Bricolage, Digital Transformation, and Business Model Innovation: Based on the Conditional Process Analysis of Entrepreneurship - Xinyuan Wang; Zhenyang Zhang; Dongphil Chun (Systems)
Business model innovation represents a critical pathway for firms to create value and enhance competitiveness, yet innovation processes are frequently constrained by resource limitations. To explore the determinants of business model innovation, we developed a theoretical framework examining the influence mechanism of resource bricolage on business model innovation, introducing digital transformation as a mediating variable and entrepreneurship as a moderating variable. We conducted an empirical study by surveying 263 entrepreneurs across China. Using Model 59 in the PROCESS macro for SPSS, we performed conditional process analysis, revealing that both resource bricolage and digital transformation positively influence business model innovation, and resource bricolage facilitates digital transformation. Furthermore, digital transformation partially mediates the relationship between resource bricolage and business model innovation, while entrepreneurship positively moderates the relationships among resource bricolage, digital transformation, and business model innovation, with higher levels of entrepreneurship demonstrating stronger moderating effects. Our findings suggest that organizations pursuing business model innovation must consider the integrated effects of multiple factors within a systems perspective.